PENGARUH PROMOSI, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Rahma Rahmi Collection) - Naufal, Arif Rahman; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
This study aims to determine the effect of promotion, price, and service quality, of purchasing decisions at Rahma Rahmi Collection Shop. The independent variable are promotion, price, and service quality affect the purchase decision as the dependent variable. The population of this study were customers of Rahma Rahmi Collection Shop, 75 responder was selected using nonprobability sampling technique. The purpose sampling is a technique to select sample only from responder who has using and buying product from Rahma Rahmi Collection Shop. The purpose of using purpose sampling technique is to make sure that the selected responder really know and familiar with Rahma Rahmi Collection Shop.Base on the result study, obtained the following equation of regression : Y1 = 0,316X1 + 0,263X2 + 0,233X3. Base on statistical analysis, indicator at this research have the character of valid and its variable have the character of reliable. On the classic assumption examining the free multicolonierity-regression model, it might not done heteroscedisty and normally distributed. Individually, the variables have greater influence is promotion variable with a regression coefficient 0,316, followed by price 0,263 and service quality 0,233. Hypothesis testing used t tests showing that the three independent variables are promotion (X1), price (X2), and service quality (X3) which investigated proved positively and significantly affect the dependent variable is the purchase decision (Y). Then through the F test can be seen that the variables product quality, promotion, and service quality eligible to test the dependent purchasing decisions. Adjusted R Square explained figures that 36,9% of purchase decisions variation can be explained by the three independent varibles in regression equations. While the rest of 63,1%was explained by other variable outside of the three variables used in this study.